New Neurons in the Dentate Gyrus Promote Reinstatement of Methamphetamine Seeking - Mandyam, Chitra D (J Exp Neurosci, 2018)
Addictive drugs effect the brain reward circuitry by altering functional plasticity of neurons governing the circuits. Relapse is an inherent problem in addicted subjects and is associated with neuroplasticity changes in several brain regions including the hippocampus. Recent studies have begun to determine the functional significance of adult neurogenesis in the dentate gyrus of the hippocampus, where new neurons in the granule cell layer are continuously generated to replace dying or diseased cells. One of the many negative consequences of chronic methamphetamine (METH) abuse and METH addiction in rodent and nonhuman primate models is a decrease in neural progenitor cells in the dentate gyrus and reduced neurogenesis in the granule cell layer during METH exposure. However, the number of progenitors rebound during withdrawal and abstinence from METH and the functional significance of enhanced survival of the progenitors during abstinence on the propensity for relapse was recently investigated by Galinato et al. A rat model of METH addiction in concert with a pharmacogenetic approach of ablating neural progenitor cells revealed that neurogenesis during abstinence promoted a relapse to METH-seeking behavior. Biochemical and electrophysiology studies demonstrated that an increase in neurogenesis during abstinence correlated with increases in plasticity-related proteins associated with learning and memory in the dentate gyrus and enhanced spontaneous activity and reduced neuronal excitability of granule cell neurons. Based on these findings, we discuss the putative molecular mechanisms that could drive aberrant neurogenesis during abstinence. We also indicate forebrain-dentate gyrus circuits that could assist with aberrant neurogenesis and drive a relapse into METH-seeking behavior in METH-addicted animals.